„Working Class, Unite, Unite…“: A few Notes on an Article by M. Pullmann and J. Rákosník - Kostlán, Antonín (Dějiny – teorie – kritika, 2007)
In this article, the author takes on certain ideas presented in an essay by Michal Pullmann and Jakub Rákosník published in this number of this journal – concretely, with their view that the concept of the „working class“ should be reinstated in Czech historical research as an instrument suitable for analysing modern social developments. In this connection, the author draws attention to three groups of issues: modern – chiefly sociological – critiques regarding the use of this instrument for analysing social phenomena; questionable concepts of „class identity“ and „class consciousness“ which Marxist conceptions of (the working) class as a social stratum reduce to the level of a merely manipulative ideological tool; and the role which the erstwhile communist regime assigned to the term „working class“ in legitimising its violent seizure of power and its subsequent crimes.